Improvements to suicide preventive therapeutic practices in the brazilian Unique Health System – UHS - Hering , Maria Júlia Zimmermann; Broering , Camila Purnhagen; Ribeiro , Ricardo Crisóstomo; Cunha , Angela Duebbers; Nunes , Carlos Roberto de Oliveira (Seven Editora, 2023)
Suicide is a public health problem. Besides the reduction in suicide taxa worldwide, in Brazil, this index is still growing. The adult population presented the bigger taxa of suicide mortality. Because of this, review the literature to identify preventive practices that can contribute to the improvement of current methods in the Brazilian Unique Health System. Were reviewed articles from PubMed and LILACS databases, applying the key words suicide, prevention and intervention, and the criteria of time among 2015 to 2020, available as an open-access resource. Following these criteria were analyzed three articles with studies carried out in Europe and focused on preventive practices against suicide. Obtaining that all new therapeutic involve self-report analyses due to confidence relationships between psychotherapists and patients. Applied psychometric tests are simple, analytically consistent, and easily adaptable to all health systems, measuring the suffering levels or possible suicide ideation. In Brazil, the Psychosocial Centers receive and follow patients with multiple psychological and/or psychiatric disorders. However, still hasn’t been a standard to evaluate psychological suffering or even good practices to prevent suicide. As the main result, the present literature review indicated the alternatives to improves psychological reception to patients with suicide ideation. Suicide prevention through psychometric evaluations represents more than an alternative to reduces this class of intentional death. Implies in reductions of public investments to treatment, and patients live quality improvement through their life. DOI:https://doi.org/10.56238/interdiinovationscrese-037